PENINGKATAN KARIR GURU DI SMK SWASTA BM TELADAN MEDAN - Charles Fransiscus Ambarita (Jurnal Guru Kita PGSD, 2018)
Abstract: Teacher Career Improvement in BM Exemplary Private VocationalSchool Medan. Survey Sites at BM Teladan Jl. Pukat IV No. 52, Bantan TimurVillage, Medan Tembung Subdistrict, Medan, North Sumatra. The time of thesurvey was conducted in February 2018. All subjects in the BM ExemplaryVocational School were the subjects in this study. The technique of collecting datathrough interviews and direct observation to the Exemplary BM Vocational Schoolwith speakers, namely the Principal. In the field observation process, there are stillmany teachers who have not been certified even though they have become seniorteachers, there are still many teachers who have not been able to apply various typesof learning models, and many teachers who have not been able to use learningmedia. This problem causes the teacher to hamper in developing his career. Basedon the results of research at the BM Exemplary Private Vocational School, Medan,data obtained that the number of teachers who have carried out professionalizationin the development of teacher careers is still relatively low. Of the 22 teachers therewere only 11 teachers who had made certification.Keywords: Teacher's Career, Teacher Professionalism, Teacher CertificationAbstrak: Peningkatan Karir Guru di SMK Swasta BM Teladan Medan.Tempat Survey di SMK BM Teladan Jl. Pukat IV No. 52, Kelurahan Bantan Timur,Kecamatan Medan Tembung, Medan, Sumatera Utara. Waktu survey dilakukanpada Februari 2018. Yang menjadi subjek dalam penelitian ini adalah semua guru diSMK BM Teladan. Teknik pengambilan data melalui wawancara dan observasilangsung ke SMK BM Teladan dengan narasumber yaitu Kepala Sekolah.Padaproses observasi dilapangan ditemukan masih banyak guru yang belum sertifikasimeskipun sudah menjadi guru senior, masih banyaknya guru yang belum mampumenerapkan berbagai macam model pembelajaran, dan masih banyak guru yangbelum dapat menggunakan media pembelajaran. Permasalahan inilah yangmenyebabkan terhambatnya guru dalam mengembangkan karirnya. Berdasarkanhasil penelitian di SMK SWASTA BM Teladan Medan, diperoleh data bahwajumlah guru yang telah melaksanakan profesionalisasi dalam perkembangan karirguru masih tergolong rendah. Dari 22 guru hanya terdapat 11 guru yang telahmelakukan sertifikasi.Kata Kunci : Karir Guru, Profesionalitas Guru, Sertifikasi Guru